Total and Authoritary State Regimes - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2021)
This scientific article analyzes and dialectically evaluates non-democratic state regimes, which, from the position of the author, cannot be definedas anti-democratic regimes. This assessment of the undemocratic state regime is transferred to its two main varieties - authoritarian and totalitarian regimes, focusing on the negative and positive aspects of both. Special attention is paid to the problem of correlation between totalitarian and authoritarian state regimes.